2018
DOI: 10.1155/2018/4176803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bhramari Pranayama on the Acoustic and Aerodynamic Parameters of Voice in Normophonic Females

Abstract: Summary. Objective Pranayama is known for improving various health conditions. The present study is aimed at investigating the effects of bhramari pranayama on aerodynamic and acoustic parameters of voice in healthy individuals. Study Design This is a pretest-posttest design study. Methods A total of 24 participants in the age range of 20 to 25 years completed the bhramari pranayama regimen for 30 sessions. Aerodynamic and acoustic assessments were done before and after pranayama sessions. Maximum phonation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…Another study [17] was done in individuals who practiced Bhramari Pranayama and adjudged that mean MPD increased for all vowels after practicing Bhramari pranayama. A study [18] on the result of aerobic training and hatha yoga on vital capacity, found out that Aerobic training, hatha yoga, and blend of aerobic and hatha yoga training added significant outcome on the vital capacity of the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [17] was done in individuals who practiced Bhramari Pranayama and adjudged that mean MPD increased for all vowels after practicing Bhramari pranayama. A study [18] on the result of aerobic training and hatha yoga on vital capacity, found out that Aerobic training, hatha yoga, and blend of aerobic and hatha yoga training added significant outcome on the vital capacity of the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the practice of Bhramari pranayama may be helpful in improving the respiratory phonatory coordination and also that with extensive practice one can achieve breathe control. [37] Bhramari Pranayama and Yoga Nidra if practiced together can significantly alleviate the stress induced changes in cardio-respiratory parameters. Yoga is undoubtedly a trouble-free and cost effective way for reducing damaging effects of stress and if incorporated in our lifestyle yoga can honour us with a long, healthy and disease-free life.…”
Section: Other Effects Of Bhramari Pranayamamentioning
confidence: 99%
“…Humming bee breathing technique has proved to be effective in changing the cardiovascular parameters and pulmonary functions [ [6] , [7] , [8] , [9] , [10] ]. Authors have previously reported that humming bee breathing practice resulted in changes in acoustic and aerodynamic parameters of voice, as well as giving a fine resonant voice quality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%